Impact of Clinical Pharmacist Mediated Patient Counselling on Health Related Quality of Life in Hypertensive Patients - B, Naveen.; M, Mahaboojan.; R, Padmanabha Y; G, Narayana. (Indian Journal of Pharmacy Practice)
Hypertension is a major risk factor to many diseases like myocardial infarction, stroke, heart failure, renal failure, and retinopathy which is a leading cause of death.Only two-thirds of patients with hypertension are aware of their status, which means that a large segment of the population has hypertension that is unrecognized and untreated.This study aims to provide patient counseling regarding risk factors, life style modifications and pharmacological therapy by orally and through patient information leaflet which will improves KAP and Health related quality of life in hypertension. At baseline there was no significant difference between the mean blood pressure, HRQoL score and KAP of the test and control groups At final follow up test group patients had significantly (p=0.021) higher QoL scores than at baseline. Patient in the test group had very significant improvement in the KAP score. At the end of the study the patients in the test group had better blood pressure control values and better scores in all six subscales of the SF-36v2 health survey questionnaire. These patients also showed improved KAP scores at the final follow up. Our study concludes that clinical pharmacist can play an important role in improving the treatment outcomes and quality of life of patients with hypertension.
Keywords: hypertension; health related quality of life; counseling